Leading a virtual exercise program: Student motivation and perception of participation benefits - Jena Buchan; Kelly Clanchy; Nathan Reeves (Bond University, 2021)
_Introduction:_ Work-integrated learning (WIL) is integral to exercise science degrees, but clinical educators report low motivation and limited professional competency in students. WIL may be enhanced by first building professional capabilities in a University-based setting. As such, this study investigated whether participation in a student-led virtual exercise clinic improved perceived professional self-efficacy, as well as intrinsic motivation. _Methods:_ A prospective, repeated-measures cohort design. Exercise Science Practicum students (N= 20) delivered a six-week virtual exercise program. Outcomes of interest included changes in client-related skills confidence (e.g. interpersonal skills) and perceived participation benefits and motivation (p < 0.05). _Results:_ Seventeen students (85%) completed the survey, reporting significant improvement (Z= -3.18) in confidence related to client communication skills. Additionally, students reported significantly higher perceived truthfulness of statements in the intrinsic motivation subscales: interest-enjoyment (Z= -2.77); perceived competency (Z= -2.80); and value-usefulness for the development of communication skills (Z= -2.33). _Discussion:_ Participation in a virtual student-led exercise clinic enhanced confidence in client-related communication skills, as well as multiple intrinsic motivation domains. With an increased need for developing student competency and motivation for WIL, virtual student-led clinics may prove a novel enabler.